Chthonius (Globochthonius) montis n. sp.: A new epigean pseudoscorpion from Montenegro (Chthoniidae, Pseudoscorpiones) - Ćurčić B.P.M.; Dimitrijević R.N.; Ćurčić S.B.; Makarov S.E.; Ćurčić Nina B.; Tomić V.T.; Ilić B.S. (Archives of Biological Sciences, 2013)
A new endemic epigean pseudoscorpion species from Mt. Orjen, Montenegro, is presented, described, and illustrated. Its main morphometric characters and important diagnostic features are analyzed and compared to its closest congeners. [Projekat Ministarstva nauke Republike Srbije, br. 173038]